Improvement of growth rates and nutritional contents of freshwater microalgae through bacteria-microalgae interaction - Noor Mazli, Nur Amirah Izyan (2022)
Microalgae have been utilized extensively for decades in various applications, including aquaculture nutrition, to boost the growth and health of aquatic species. Although microalgae have high biomass production per unit area, their growth rate and biochemical compositions are heavily influenced by abiotic and biotic variables, including contamination by microorganisms. Nonetheless, bacteria are no longer seen as mere contamination to the cultures, as the symbiotic microalgae-bacterial interactions may benefit both populations and be exploited for aquaculture use. This study was conducted to develop a bacteria-microalgae consortium with improved nutritional content and biomass production to be used as live feed. Ten freshwater microalgae strains (Chlorella sp. (UPMC-A0088), Chlamydomonas reinhardtii (UPMC-A0054), Scenedesmus obliquus (UPMC- A0057), Scenedesmus communis (UPMC-A0061), Oocystis sp. (UPMC-A0084), Poteriochroomonas malhamensis (UPMC-A0073), Pavlova noctivaga (UPMC- A0072), Navicula permitis (UPMC-A0071), Nitzschia palea (UPMC-A0058), Cyclotella meneghiniana (UPMC-A0070)) obtained from microalgae culture collection of Laboratory of Aquatic Animal Health and Therapeutics, Institute of Bioscience, Universiti Putra Malaysia were grown in Bold Basal medium at pH 6.8 ± 0.2 under a light intensity of 120 μmol photons m−2s−1 at 25 ± 2°C. The growth rate assessment of the microalgae was carried out, followed by biochemical analyses of total carbohydrate, protein, lipid, and fatty acid compositions. Among the ten microalgae, Scenedesmus communis, Navicula pemitis and Cyclotella meneghiniana showed significantly (P < 0.05) higher specific growth rates (0.23-0.37 day-1) and biochemical contents (19.96-52.05% DW carbohydrate, 32.27-46.94% DW protein and 17.22-19.72% DW lipid). Subsequently, to isolate microalgae growth-promoting bacteria (MGPB) from the phycosphere, microalgae cells of the ten species were collected at exponential phase, washed, and subjected to centrifugation and sonication to separate bacteria from microalgae colonies. The samples were cultured onto five different medium agar which suited bacterial growth; Alkaline Nutrient (AN), Mueller Hinton (MH), Glucose Peptone Water (GPW), Thiocitrate Bile-salt Sucrose (TCBS), De Man and Rogasa (MRS). Morphologically distinct colonies were selected, purified, and stored at −20°C for further use. A total of 80 bacterial isolates were screened for their microalgal growth-promoting traits, whereby indole acetic acid (IAA) production, phosphate solubilizing, and nitrogen-fixing abilities were tested. Only seven isolates were recorded to have the multiple MGP traits, with three strains; CY-2, CY-4, CY-5 showing the highest (P < 0.05) record for indole acetic acid (IAA) production, as well as phosphate solubilizing and nitrogen-fixing abilities. These seven potential MGPB were molecularly characterized using 16S rRNA approach and the data sequences were deposited into Genbank to get the accession number (MW301667-MW301673). Subsequently the co-cultivation effect of the best three MGPB on the growth and nutritional content of the best three microalgae strains were assessed. Ochrobactrum haematophilum was discovered to considerably (P < 0.05) improve the specific growth rate (0.38-0.64 day-1) and nutritional contents (17.76- 33.40% DW carbohydrate, 30.53-37.49% DW protein, 22.09-22.50% DW lipid) of microalgae S. communis, N. permitis and C. meneghiniana up to two-fold increase. This study has shown that bacterium isolated from the phycosphere of microalgae Cyclotella meneghiniana, Ochrobactrum haematophilum may have microalgae growth-promoting traits that aid in the development of bacteria- microalgae consortium that can be utilized as a high-quality live feed in aquaculture.